Analisis Pelaksanaan Program Pelatihan dan Pengembangan Karyawan: Studi Kasus Pada PT Visi Sukses Bersama Jakarta - R Ati Haryati (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
The importance of employee training and development programs are becoming a necessity for companies who want to increase the capabilities, knowledge, and experience of the employees in the company. Issues that arise in training and development undertaken by the company often have yet to match the needs of the company, and an individual assignment so  that it does not support the work achievement and career employees. PT Visi Sukses Bersama working to improve employee productivity by conducting employee training and deplopement program for 3 (three) months, its aim is go that employees who have been selected in stage of recruitmen and selection exercise his duties well and reduce errors or gaps in the knowlege owned by the employees. The methods used in this research is descriptive qualitative data collection methods, namely observation, interviews and documentation study. Procedures training in PT Visi Sukses Bersama using methods on the job training (rotation position, training, internship and job supply). To assess the programmes that had been held by PT Visi Sukses Bersama, then held an evaluation regarding training and deveploment, whether the targets that have been set are achieved or not.